2014
DOI: 10.1055/s-0034-1372644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Escitalopram on Plasma Concentrations of Aripiprazole and its Active Metabolite, Dehydroaripiprazole, in Japanese Patients

Abstract: Introduction: The effects of escitalopram (10?mg/d) coadministration on plasma concentrations of aripiprazole and its active metabolite, dehydroaripiprazole, were studied in 13 Japanese psychiatric patients and compared with those of paroxetine (10?mg/d) coadministration. Methods: The patients had received 6?24?mg/d of aripiprazole for at least 2 weeks. Patients were randomly allocated to one of 2 treatment sequ?ences: paroxetine-escitalopram (n=6) or escitalopram-paroxetine (n=7). Each sequence consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The pharmacogenetic profile of the population (CYP1A2 HI: 0.86; CYP2D6 EM: 0.85; CYP3A4 EM: 0.91) could explain the need to apply a higher dose with its consequent adverse effects in patients treated with olanzapine [41], clozapine [42], or asenapine [43], all related to CYP1A2, while favoring the use of aripiprazole or risperidone in those who have a wt-like haplotype in CYP2D6 [44][45][46][47][48][49] and CYP3A4 [44,50] cytochromes, a situation frequently found in our population.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacogenetic profile of the population (CYP1A2 HI: 0.86; CYP2D6 EM: 0.85; CYP3A4 EM: 0.91) could explain the need to apply a higher dose with its consequent adverse effects in patients treated with olanzapine [41], clozapine [42], or asenapine [43], all related to CYP1A2, while favoring the use of aripiprazole or risperidone in those who have a wt-like haplotype in CYP2D6 [44][45][46][47][48][49] and CYP3A4 [44,50] cytochromes, a situation frequently found in our population.…”
Section: Discussionmentioning
confidence: 99%
“…The mood stabilizers carbamazepine and valproate were found to decrease ARI (AM) BLs by 65% and 23%, respectively (Nakamura et al 2009;Eryilmaz et al 2014). No influence of escitalopram (Nemoto et al 2014), haloperidol (Nakamura et al 2014) or clozapine (Zuo et al 2006) coadministration was found. Concurrent treatment with CYP3A4 inducers, CYP2D6 inhibitors, alimemazine, or lithium changed BLs by 40%-60%, which has to be considered clinically relevant (Waade et al 2009).…”
Section: Concomitant Medicationmentioning
confidence: 90%
“…This finding was confirmed in another study (Nemoto et al 2012). The same group was not able to replicate this result (Nemoto et al 2014). A Japanese study found that dose-corrected ARI and AM concentrations increased with a general increase in the number of the mutated CYP2D6 alleles *5, *10, and *14 (Nagai et al 2012).…”
Section: Cyp2d6 Genotypingmentioning
confidence: 93%
See 1 more Smart Citation
“…The presence of duplication in the absence of inactive or reduced-activity alleles results in an ultrarapid metabolizer (UM) [46]. PM individuals were found to have higher aripiprazole/risperidone active moieties exposure [21,28,[47][48][49][50][51], with this exposure even being proportional to the number of affected alleles in some studies [47,48]. Furthermore, it has been found that PM individuals tend to have lower aripiprazole/risperidone doses administered, as it has been recommended in some studies [28,52], and, alongside UM individuals, have a higher risk of risperidone treatment failure [51].…”
Section: Cyp2d6mentioning
confidence: 99%